Basis of Products Collective Civil Liability: A Comparative Analytical Study - Omed Sabah Othman; Mukrian Aziz Muhammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
With the development of Science, and Mankind, and the increase in his daily needs, especially in terms of satisfying these needs, the importance of the Collective Civil Liability system has increased and has become the subject of controversy and research for many jurists of civil law. And Collective Civil Liability in particular, has a great importance in our daily life. Today a number of modern theories have emerged as a basis for Collective Civil Liability such as Negligence and Strict Liability. Each of them has his arguments and supports. Civil Liability in general and Collective Civil Liability in particular are to compensate for the damages that a person may cause to another, whether this damage was caused by a Contract or from a Harmful act, and this Liability must be based on a legal basis upon which it is based, and studying this basis means standing on The wisdom for which the legislator has embarked on this Liability is thus constituting one of the legal systems within the scope of the Civil Law, and the establishment of Liability cannot be justified without a foundation on which to base it, without finding the appropriate basis for the Collective Civil Liability we cannot establish on the Producers and therefore this indicates our inability to establish Civil Liability collectively relying on the old Basis of Liability in the Iraqi Laws adopted at the present time, therefor we have to establish the liability on the modern basis.